Third world multinationals : - Beausang, Francesca (Palgrave Macmillan, 2003)
This book evaluates the contribution of third world multinational enterprises to the competitiveness of their home and host countries in the context of Brazilian and Chilean MNE's. This book fills the gap in the literature by looking at third world MNE's ability to innovate and examining the potential for their innovations to be diffused to other home country firms and thereby improve their home country's competitiveness.